Physical and Mechanical Properties of Synthesized Doped Nanoferrite - Chyad, Fadhil A.; Hamza, Mohammed S.; Dhary, Zainab I. (Al-Khwarizmi Engineering Journal, 2017)
Nanoferrite materials have been synthesized by sol-gel auto combustion method. The effect of doping different percentages of Y2O3 (0.34 µm) on the physical and mechanical properties of selected mixed ferrite [(Li2.5Fe0.5) 0.9(Co4Fe2O4) 0.1] by adding 10% Cobalt ferrite was studied. Physical properties (i.e. .density, porosity and water absorption) were affected by the doping, where the density increased about 32% at 6 wt% Y2O3, while porosity has a drastically decreased about 80% at 6% Y2O3 and has a correlation effect on the mechanical properties(Splitting  tensile strength and Vickers microhardnss). The fracture strength at 1 % wt. of  Y2O3 has doubled value of the undoped sample and then decreased. The same behavior shows with the testing of Vickers micro hardness.SEM ( Scanning electron microscopy ) micrographs revealed that the microstructure of the fracture surface of the samples consist of detached approximately closely packed particles and also showed the formation of micro agglomerated particles with some voids . By doping with Y2O3 the pores decreased and a dense material obtained